Crisis Communication During COVID-19 Pandemic: Lessons from Universitas Muhammadiyah Yogyakarta - rosilawati, yeni; Winarsih, Atik Septi (Jurnal Ilmu Komunikasi, 2023)
The COVID-19 pandemic has devastated the global population, disrupting many aspects of human life, including education. Countries like Indonesia have implemented policies requiring schools, colleges, and universities to be closed. This research aims to develop crisis communication guidelines specifically adapted for higher education institutions to prevent the spread of the virus. One higher education institution, Yogyakarta Muhammadiyah University (UMY), has switched from traditional face-to-face lectures to online learning. This study used a qualitative approach, data collection techniques of in-depth interviews with the UMY Public Relations Bureau, the UMY Planning and Development Agency (BPP), students, and document analysis to examine crisis communication management strategies implemented by universities during the pandemic. The study results found a crisis communication model used by students, parents, educators, and employees to continue learning and working safely and comfortably despite the spread of COVID-19. The latest information can be found on https://COVID 19.umy.ac.id/ and UMY’s official social media. This research contribution includes the integration of theory, practical applications, empirical insights, and a deeper understanding of crisis communication strategies in the context of higher education institutions and government responses to the COVID-19 pandemic.